Analysis of temperature field and convection heat transfer of oil-air two-phase flow for ball bearing with under-race lubrication. Issue 5 (13th July 2021) - Bao, Heyun; Hou, Xiaonan; Tang, Xin; Lu, Fengxia
Abstract : Purpose: Under-race lubrication can increase the amount of lubricating oil entering a bearing and greatly improve lubrication and cooling effects. The oil-air two-phase flow and heat transfer characteristics inside a ball bearing with under-race lubrication play a key role in lubrication and cooling performance. The purpose of this paper is to study these two characteristics, and then provide guidance for lubrication and heat dissipation of bearing with under-race lubrication. Design/methodology/approach: In this paper, a simplified three-dimension heat transfer model of ball bearing with under-race lubrication is established; the coupled level set volume of fluid method is used to track the oil-air two-phase flow, and the Palmgren method is used to calculate the heat generation. The influence of rotation speed and inlet velocity on oil volume fraction, temperature and convection heat transfer is investigated. A temperature test for under-race lubrication is carried out. Findings: Because of the centrifugal force, lubricating oil is located more on the outer ring raceway. As the rotation speed decreases and the inlet velocity increases, the oil volume fraction increases and the temperature decreases. Furthermore, the area with high oil volume fraction has a large convection heat transfer coefficient and low temperature. The error between the simulation temperature and the test temperature is within 10%. Originality/value: The research on the temperature field and convection heat transfer characteristics of under-race lubrication ball bearings at different rotation speeds and inlet velocities is rarely involved.